Protein digestibility of textured-wheat-protein (TWP) -based meat analogues: (I) Effects of fibrous structure. (September 2022) - Lin, Quanquan; Pan, Libing; Deng, Ninghua; Sang, Mengli; Cai, Keteng; Chen, Chuling; Han, Jianzhong; Ye, Aiqian
Abstract: This study aimed to investigate the effects of fibrous structure under different moistures during extrusion on the protein digestibility of textured-wheat-protein (TWP) -based meat analogues. Three TWPs (TWP-1, TWP-2, TWP-3) were prepared under an extrusion moisture content of 26.5%, 29.3% and 32.0%. The fibrous structure was analysed through determining the texture properties, degree of texturisation, microstructure of TWPs, and chemical bonds of proteins. When the extrusion moisture increased from 26.5% to 32.0%, the hardness, and degree of texturisation of TWP increased from 2067.1 ± 606.7 g and 2.16 ± 0.13 to 2681.8 ± 359.7 g and 3.55 ± 0.22, respectively, while the cohesiveness decreased from 0.581 ± 0.061 to 0.394 ± 0.033 with less compact fibers. Changes in the particle size and distribution, SDS-PAGE, soluble nitrogen content, and free amino acids of digesta were determined during digestion. It was found that the TWP prepared under a lower extrusion moisture content had a bigger particle size of both gastric and small intestinal digesta. The combination of the results of SDS-PAGE, the soluble nitrogen content, and free amino acids of digesta showed the digestion of protein in TWPs was greater than that in the control sample, and the breakdown rate and proteolysis degree in TWPs increased with the increase in the degree of texturisation of TWP. After the small intestinal digestion, the release of free amino acids in the TWP-1, TWP-2, TWP-3, and the control sample were 375.1 ± 1.4, 489.5 ± 0.8, 475.0 ± 1.6, and 262.3 ± 0.8 mg/10 g digesta. The lower degree of proteolysis in the TWPs prepared under a lower moisture content may be due to its smaller gaps between fibers with greater cohesiveness. Graphical abstract: Image 1 Highlights: The extrusion moisture of TWPs had significant effects on their fibrous structure. Higher extrusion moistures resulted in larger gaps between fibers in TWPs. The fibrous structure affected the wheat protein digestion in TWPs. The proteolysis degree in TWPs increased with the extrusion moisture content. Smaller gaps between fibers in the TWPs led to a lower degree of proteolysis.